2021
DOI: 10.1111/jre.12855
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing citric acid protocol to control implant‐related infections: Anin vitroandin situstudy

Abstract: Objective The present study aimed to establish an optimized protocol for biofilm removal from titanium (Ti) surfaces using citric acid (CA) solutions. Background Biofilm accumulation is the main factor to trigger peri‐implant infections and to increase the risk of treatment failures. Although CA has been suggested as the anti‐infective agent with highest potential for biofilm removal on Ti, there is no consensus that CA could improve the anti‐infective treatment and its effect. Methods Physical and chemical al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 52 publications
(87 reference statements)
0
6
0
Order By: Relevance
“…As the biofilm develops, oxidation reactions due to bacterial acidic metabolites and oxygen level deficiency may occur between the biofilm-covered Ti surface (cathodic area) and the exposed Ti (anodic area), increasing the corrosion rate of the implant material [ 17 ]. Additionally, biofilm decontamination by mechanical debridement and chemical methods, such as citric acid rubbing, may also induce Ti release from the implant surface [ 30 , 31 ].…”
Section: Dental Implants Meet the Challenges Of The Reactive Oral Environmentmentioning
confidence: 99%
“…As the biofilm develops, oxidation reactions due to bacterial acidic metabolites and oxygen level deficiency may occur between the biofilm-covered Ti surface (cathodic area) and the exposed Ti (anodic area), increasing the corrosion rate of the implant material [ 17 ]. Additionally, biofilm decontamination by mechanical debridement and chemical methods, such as citric acid rubbing, may also induce Ti release from the implant surface [ 30 , 31 ].…”
Section: Dental Implants Meet the Challenges Of The Reactive Oral Environmentmentioning
confidence: 99%
“…While Er:YAG laser (AlMoharib et al, 2021; Eick et al, 2017) and air‐abrasive devices (Keim et al, 2019; Leung et al, 2022; Tuchscheerer et al, 2021) proved to be effective, curettes and sonic / ultrasonic devices cleaned the surfaces poorly (AlMoharib et al, 2021; Keim et al, 2019; Sahrmann et al, 2015). Chemotherapeutic agents such as chlorhexidine, phosphoric acid (Dostie et al, 2017) citric acid (Cordeiro et al, 2021; Kotsakis et al, 2016), and NaOCl‐EDTA (Kotsakis et al, 2016) demonstrated modest and favorable antimicrobial effects on biofilms on titanium surfaces. Thereby, a few of the aforementioned studies used multispecies biofilm models (Cordeiro et al, 2021; Eick et al, 2017) or plaque samples from subjects (AlMoharib et al, 2021; Dostie et al, 2017; Wheelis et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Chemotherapeutic agents such as chlorhexidine, phosphoric acid (Dostie et al, 2017) citric acid (Cordeiro et al, 2021; Kotsakis et al, 2016), and NaOCl‐EDTA (Kotsakis et al, 2016) demonstrated modest and favorable antimicrobial effects on biofilms on titanium surfaces. Thereby, a few of the aforementioned studies used multispecies biofilm models (Cordeiro et al, 2021; Eick et al, 2017) or plaque samples from subjects (AlMoharib et al, 2021; Dostie et al, 2017; Wheelis et al, 2016). Furthermore, there is growing but still limited evidence about cytocompatibility of decontamination methods (Kotsakis et al, 2016; Ungvári et al, 2010; Wheelis et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Processing of titanium and its alloys has been done through several approaches. These include, but are not limited to, new alloy formation, laser or UV treatment, antimicrobial peptides, plasma spraying, anodization, silanization, antimicrobial coatings, and photolithography. , Most of these studies have reported comparisons of the attachment behavior of multiple species on the modified and control surfaces. The bacterial species tested in several studies have been categorized under the yellow (early), orange (intermediate), or red complexes (late colonizers), Table .…”
Section: In Vitro In Vivo and Clinical Studies Of Titanium Dental Imp...mentioning
confidence: 99%